General Medical Service for the Nation : The Question of Medical Institutions and Hospitals
1938-07-06 1938 1930s 4 pages PRIVATE & CONFIDENTIAL. Soc.Ins.Cttee.10/2(1937-38). 6th July, 1938. TRADES UNION CONGRESS. GENERAL MEDICAL SERVICE FOR THE NATION. THE QUESTION OF MEDICAL INSTITUTIONS AND HOSPITALS. See paragraphs 40-44, pp.21-23; and paragraphs 56-75, pp. 28-35, of the B.M.A. "General Medical Service for the Nation". 1. Apparently the British Medical Association proposes in their "General Medical Service for the Nation" to leave the present hospital services of the country practically as they are to-day. There are very few alterations or modifications suggested, except with regard to some tentative proposals for co-operative and inter-consultative machinery, the staffing of hospitals, the payment of hospital staffs, and the revision of the out-patient department, so that the machinery regarding patients should filter through the general practitioner medical service. 2. The hospitals of the country can be mainly divided into two types: (1) the Voluntary Hospital, which can be discussed separately as a voluntary hospital system, and (2) the Municipal Hospitals, which can be discussed under the institutions of Local Authorities. 3. The Voluntary Hospital, which at one time depended almost entirely on the contributions of large subscribers and had self-selective Boards of Management, has been gradually changing with the gradual change in social conditions and circumstances in Great Britain. At one time it was a place where the poor could obtain treatment without any question of payment for the services rendered. It was a purely philanthropic and medical institution. There were certain medical gains as there are at present to the medical consultants on the medical staffs of the hospital, especially in teaching schools, in that, first, they not only gained experience from the cumulative effect of the practice of their profession and the difficult or unusual cases coming to the hospital, but also from the point of view of contact with medical students - the prospective medical practitioners of the future - who in their private practices would tend to send their difficult private cases, who could afford to do so, to these consultants at their private rooms. But at the hospital itself an almost complete medical service was provided for the poor without any payment. Gradually, however, this system has been changing, until at the present time, with the increased cost of administration and the increased cost of equipment, with, at the same time, a tendency to the drying up of private subscriptions, there has been a specialised service to the great majority of the population, not only to those who cannot afford to pay anything, but, as the B.M.A. admits, to those who can and do pay in part or in whole for the service they receive. 292/842/2/229